1975
DOI: 10.1002/1097-0142(197507)36:1<240::aid-cncr2820360127>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Extraskeletal neoplasm resembling Ewing's sarcoma

Abstract: This article reviews the pathologic features and the behavior of 39 small, round, or oval cell sarcomas occurring in the soft tissues and considered histologically indistinguishable from Ewing's sarcoma of bone. The tumors affected chiefly young adults (median age 20 years) and most commonly involved the soft tissues of the lower extremity and the paravertebral region. Microscopically, they consisted of solidly packed small, round, or ovoid cells of great uniformity, arranged in sheets or lobules separated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
213
0
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(223 citation statements)
references
References 19 publications
3
213
0
2
Order By: Relevance
“…2), which is consistent with previously reported histological findings (Angervall and Enzinger 1975;Ahmad et al 1999). Rosette-like structures were infrequently seen.…”
Section: Histological Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…2), which is consistent with previously reported histological findings (Angervall and Enzinger 1975;Ahmad et al 1999). Rosette-like structures were infrequently seen.…”
Section: Histological Findingssupporting
confidence: 91%
“…Angervall and Enzinger (1975) first reported the pathological features and the behavior of EES, which are round, or oval cell sarcomas occurring in the soft tissues, and they also reported that this tumor wad histologically indistinguishable from Ewing's sarcoma of bone. The tumors affect mostly young adults (median age 20 years) and most commonly involve the soft tissues of the lower extremity and the paravertebral region.…”
Section: Discussionmentioning
confidence: 99%
“…On immunohistochemistry, S-100 positivity frequently is seen [13,34]. Extraosseous Ewing's sarcoma is a malignant small, round, blue-cell tumor that occurs mostly during or after adolescence, with a slight male predominance [2,31,44,52]. The extremities are the most common sites of involvement [41,48].…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…Since the first description of PNET/ES arising in superficial locations (ie, in the skin and/or subcutis) by Angervall and Enzinger in 1975, 13 32 cases diagnosed on at least histology and CD99 positivity have been reported, more often as single cases [1][2][3][4][5] with three series of 8, 5, and 13 cases. [6][7][8] A review of the reported cases (Table 7) shows that they occurred in 8 male and 24 female patients aged from 2 to 67 years (median, 18), with no site predilection.…”
Section: Discussionmentioning
confidence: 99%